Musculoskeletal Rehabilitation after Hip Fracture: A Review - Pfeifer, Michael; Dionyssiotis, Yannis (Osteologie, 2019)
With increasing longevity, hip fractures become more and more a serious burden not only for societies in developed civilization, but also for emerging countries. According to world-wide projections 1.5 million people are affected each year. Although a lot of research has been performed over the last decade, there is still a lack of standardized and evidence-based approaches for prevention, treatment, and rehabilitation of this worst complication of osteoporosis.Therefore, the evidence base for this article was synthesized in accordance with SIGN methodology. Databases searched include Medline, Embase, Cinahl and the Cochrane Library between March 1999 and March 2019. The following terms are used: osteoporosis, hip fracture, rehabilitation, falls, muscle strength, nutrition, exercise, balance, sway, and hip protectors. Moreover, reference lists from included studies were checked and author`s names were searched for additional studies.Possibly, the best approach to rehabilitation after hip fracture is a multi-disciplinary team co-ordinating medical, social, educational and vocational measure for training or retraining the individual to the highest possible level of function. In order to prevent thromboembolism low-dose anti-coagulation therapy (e. g. fondaparinux, rivaroxaban) may be used for approximately two weeks after surgery. This should be accompanied by a daily nutritional intake of at least 20 g protein, 1200 mg of elemental calcium and 800 I. U. of vitamin D, whereas in severe vitamin D insufficiencies recommendations may be certainly higher.After surgical repair of the hip fracture, an anti-resorptive medication may be started. While balance training and performing of Tai Chi has been shown to reduce fall risk and thereby also decrease hip fracture risk, the use of hip protectors is still under evaluation and cannot be generally advocated.
Keywords: Osteoporosis; hip fracture; rehabilitation; nutrition; muscle strength; exercise; hip protectors